TI_GERICHTE 12.2012.213 vom 28. April 2014 , Società anonima - contestazione di delibera assembleare - assemblea totalitaria - TI Tribunale d'appello (2014)
Società anonima - contestazione di delibera assembleare - assemblea totalitaria